Inactivation kinetics of different flexible packing materials for decontamination of yellowfin tuna Thunnus albacares using pulsed light technology - Ananthanarayanan, T. R.; Nithin, C. T.; Yathavamoorthi, R.; Panda, Satyen Kumar; Srinivasa Gopal, T. K. (Indian Journal of Fisheries, 2022)
Comparative efficiency of three different packing materials for post-packaging decontamination of yellowfin tuna Thunnus albacares steaks using pulsed light (PL) technology was investigated during the study. The packing materials used were 300 gauge low density polyethylene (LDPE), 12 Âµ polyester 300 guage polyethylene (PEST/PE) and 300 gauge cast polypropylene (CPP). Inactivation curves were plotted separately for each material for pulsed light exposure time ranging from 0 to 12 s. The curves were fitted with three different models viz, (i) log-linear, (ii) log-linear with Geeraerd and (iii) log-linear with Weibull model and corresponding goodness-of-fit statistics were estimated. Considering the least treatment time for achieving log microbial reduction, CPP was found to be the ideal choice among the three packaging materials. Among the three models, considering the lowest root-mean-square error values (0.0291, 0.0210 and 0.0141 for samples packed in LDPE, PEST/PE and CPP respectively), Weibull model was found to be most appropriate for describing the inactivation curves in all sample cases. Therefore, inactivation curves of steaks packed in CPP was validated with the Weibull model. The corresponding root-mean-square error (0.1036) and correlation coefficient (0.9974) showed that this model can be effectively utilised for modelling the microbial inactivation kinetics using pulsed light technology. Keywords: Cast polypropylene, Inactivation kinetics, Non-thermal processing, Pulsed light technology, Statistical modelling, Yellowfin tuna